One-Step RT-qPCR for Viral RNA Detection Using Digital Analysis - Park, Hyuna; Jung, Wonjong; Jang, Hyeongseok; Namkoong, Kak; Choi, Kwon-Young (Frontiers in Bioengineering and Biotechnology, 2022)
The rapid detection of viruses is becoming increasingly important to prevent widespread infections. However, virus detection via reverse transcription-quantitative polymerase chain reaction (RT-qPCR) is time-consuming, as it involves independent nucleic acid extraction and complementary DNA synthesis. This process limits the potential for rapid diagnosis and mass analysis, which are necessary to curtail viral spread. In this study, a simple and rapid thermolysis method was developed to circumvent the need for extraction and purification of viral RNA. The developed protocol was applied to one-chip digital PCR (OCdPCR), which allowed thermolysis, RT, and digital PCR in a single unit comprising 20,000 chambers of sub-nanoliter volume. Two viruses such as tobacco mosaic virus and cucumber mosaic virus were tested as model viral particles. First, the temperature, exposure time, and template concentration were optimized against tobacco mosaic viral particles, and the most efficient conditions were identified as 85°C, 5 min, and 0.01 µg/nL with a cycle threshold of approximately 33. Finally, the OCdPCR analysis yielded 1130.2 copies/µL using 10-2 µg/nL of viral particles in a 30 min thermolysis-RT reaction at 70°C. This novel protocol shows promise as a quick, accurate, and precise method for large-scale viral analysis in the future.